Yearnings in the meantime : 'normal lives' and the state in a Sarajevo apartment complex - Jansen, Stef (Dislocations, 2015)
Shortly after the book's protagonists moved into their apartment complex in Sarajevo, they, like many others, were overcome by the 1992-1995 war and the disintegration of socialist Yugoslavia More than a decade later, in post-war Bosnia and Herzegovina, they felt they were collectively stuck in a time warp where nothing seemed to be as it should be. Starting from everyday concerns, this book paints a compassionate yet critical portrait of people's sense that they were in limbo, trapped in a seemingly endless'Meantime.'Ethnographically investigating yearnings for'normal lives'in the European semi-periphery, it proposes fresh analytical tools to explore how the time and place in which we are caught shape our hopes and fears.